PENGEMBANGAN MODEL PEMBELAJARAN IPAS BERBASIS STEM-SRSD UNTUK MENINGKATKAN KETERAMPILAN NUMERASI DAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Nurhayati; Abdurrahman; Dwi Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a STEM-SRSD-based Natural and Social Science learning model to improve the numeracy and critical thinking skills of elementary school students that is valid, practical, and effective. The development of this model is motivated by the greater focus on literacy skills, while numeracy skills are often neglected, even though these skills are crucial in the modern era. Based on preliminary studies, the use of STEM approaches and SRSD strategies is still limited among teachers. Therefore, this research aims to develop a learning model that can train students' numeracy skills. This study uses a mixed-method approach with an embedded experimental model design. The development model selected is the 4D design (define, design, develop, disseminate). The research subjects consisted of 19 students in the experimental class and 18 students in the control class at SD Negeri 01 Panca Tunggal Jaya. The results showed that expert validation obtained an average score of 7.10 with a validity percentage of 78.85%, categorized as valid. The practicality test showed an average score of 95.79%, categorized as very practical. The effectiveness test showed an N-Gain of 0.74 for the experimental class (effective), while the control class had 0.04 (less effective). Therefore, the STEM-SRSD learning model is valid, practical, and effective in improving the numeracy and critical thinking skills of elementary school students, while also introducing a new learning model.